A comparison between goat milk and cow milk supplementation on nutritional status among paediatrics with cerebral palsy in Kelantan - Shamsudin, Juliana (2024)
Goat milk (GM) can be used as an alternative if cerebral palsy (CP) children are unable to tolerate cow milk. The purpose of this study was to compare the anthropometric, biochemical, clinical, and dietary intake of powdered GM versus CM among CP children in Kelantan, Malaysia. The study consists of two phases: Phase 1 focuses on determining and analysing the proximate and fatty acids profile of GM and CM, while Phase 2 involves the intervention study. In Phase 1, a grand total of 20 GM samples were analysed, along with 1 GM sample (reference) and 1 CM sample. The study’s criteria for references on GM and CM involved the use of powdered full cream milk as a primary ingredient or the most popular brand among consumers. Meanwhile, during Phase 2 of the study (quasi-experimental design, single blind), a total of 87 children with CP were randomly assigned to either goat milk (GM, n=43) or cow milk (CM, n=44). The research achieved an 82.1% response rate. The study included children between the ages of 4 and 12, but excluded those with severe cases of CP who needed special nutritional requirements such as inborn error metabolism, tube feedings, and cow milk protein allergy (CMPA). In the intervention group, the mean age was 9.05 ± 2.30 years, while in the control group, it was 8.27 ± 2.55 years. The gender distribution was as follows: in the GM group, 53.5% were male and 46.5% were female, while in the CM group, 70.5% were male and 29.5% were female. Milk powder in the form of a sachet (21-23 grams, twice a day) was provided from the start of the study until the end of the 4 months (3 meetings; baseline, 2-months, and 4-months). Anthropometric data (weight, height, BMI, MUAC, triceps and subscapular skinfold measurements, body fat percentage), biochemical data (hemoglobin and hematocrit), clinical data (systolic and diastolic blood pressure and heart rate), and dietary intake were gathered from baseline to 4-months. The Phase 1 study found that only nine GM samples out of 20 contained pure GM (based on the ingredient label), and sample G17 was chosen as goat milk for Phase 2 because it contained the highest medium-chain fatty acid (MCFA) content of 2803.9 mg (12.97%) compared to CM, 765 mg (7.19%), and the other goat milk samples. Phase 2 results show that GM showed greater improvements. There were significant differences in triceps skinfold measurement (0.33 mm vs -0.20 mm, p=0.024) and vitamin B1 (p=0.043), while other parameters did not show significant differences between GM and CM after the intervention (p>0.05). Furthermore, there was a reduction in calcium (p=0.040) and vitamin B12 (p=0.022) levels between GM and CM. In conclusion, laboratory analysis shows that GM has a higher MCFA content than CM. Meanwhile, for the intervention study, GM can be used as a tolerable supplement for CP children based solely on significant differences in triceps skinfold measurement and vitamin B1 levels. Moreover, calcium and vitamin B12 intake decreased in the daily diet of GM in comparison to CM. Further research is needed to confirm and explore this matter over a longer duration, with the necessity of conducting blood tests to assess the decrease in calcium and vitamins from the daily diet.